Characterisation of mucilage extract of Paku Midin (Stenochlaena palustris) - Wilfred, Ernielyn; Rawi, Muhamad Hanif (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2024)
Plant mucilage has a wide range of uses in the food industry. S. palustris is one of the wild plants containing mucilage, in addition, it also contains beneficial phytochemical compounds belonging to phenolic and flavonoid families. This study was conducted to determine the chemical composition of mucilage extract from S. palustris through phytochemical and physicochemical analysis, besides, determining the amount of mucilage extract yield at different maturity. The study design has two treatments, namely mucilage from young and mature leaves. Mucilage extraction is carried out using aqueous extraction technique. This research offers greater focus on specific physicochemical properties namely pH, color, and water holding capacity. The phytochemical of plant mucilages was measured using instrumental approaches of UV-Vis highlighting on phytochemical components like flavonoid and phenolic compounds. The results indicate mucilage extract of young leaves is higher than mature leaves. Meanwhile, physicochemical analysis data suggest the acid nature of mucilage is due to the presence of uronic acid, water holding capacity of mucilage from young leaves is higher than mature leaves, and each samples have obvious color differences. Phytochemical analysis reveals total phenolic content for young leaf mucilage was higher at 0.041 mg GAE/g ± 0.003, while total flavonoid content was higher in mature leaf mucilage at 0.166 mg CEQ/g ± 0.002. Overall, this study not only explains clear relationship between leaf maturity and mucilage production, but further on characterizing the physicochemical and phytochemical properties of mucilage extract from S. palustris for two different treatments.